Meningkatkan Kedisiplinan pada Pembelajaran di SD Melalui Reward dan Punishment - Ai Dalfa; Dewi Puspitasari; Fina Agustina; Silmi widiyatul awaliyah; Dhea Adela (Jurnal BELAINDIKA (Pembelajaran dan Inovasi Pendidikan), 2021)
This study aims to describe the implementation in increasing discipline in elementary school students. supporting factors, in the implementation process in increasing discipline towards elementary school children through rewards and punishments. This research use a descriptive qualitative approach. Data collection was carried out through observation, interviews, and documentation. Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that there are 3 stages in its implementation, namely through the preparation, implementation and evaluation stages. In the implementation stage, it is carried out with habituations carried out with various activities from the school. The supporting factor is the maturity of students in carrying out activities without waiting for orders from others. In addition, it is also because there are some parents who support and always monitor student activities in carrying out their learning